PEMBERIAN PASI PADA BAYI USIA 0-6 BULAN DENGAN KEJADIAN DIARE - Lina Darmayanti Bainuan (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2018)
The incidence and mortality of diarrhea in children in developing countries is still high. Moreover, in children who get formula milk, the number is significantly higher compared to children who get breast milk, which protects babies against infection. Data obtained at the DKT Hospital in Gubeng Pojok Surabaya regarding data on the incidence of diarrhea in the last three years in infants, starting from 2014-2016, concluded that from 2014-2016 at the Hospital of Gubeng Pojok Surabaya, there was an increase in the incidence of diarrhea in infants aged 0- 6 months as much as 3-4% and exceeding the tolerance level, while the tolerance rate from the Hospital of Gubeng Pojok Surabaya DKT to the incidence of diarrhea in infants is 10%. Method: This study uses analytic design with Cross Sectional Survey. The study population was all infants aged 0-6 months at the DKT Gubeng Pojok Surabaya Hospital with 1,849 infants. Sampling is done by probability sampling with systematic random sampling and a sample of 225 infants is obtained. Results: The results showed that the majority of infants who received PASI had diarrhea of ??124 infants (86.71%) compared to infants who received ASI did not suffer from diarrhea of ??62 infants (75.61%). The Chi-Square test shows the following results, that x2 counts> x2 tables (87.84> 3.84), which means there is a relationship between PASI giving to infants aged 0-6 months with the incidence of diarrhea. Discussion: there is a relationship between PASI giving to infants aged 0-6 months with the incidence of diarrhea in hospitals DKT Gubeng Pojok Surabaya. Therefore, midwives as health workers need to encourage and motivate mothers to continue to give exclusive breastfeeding 0-6 months.